Pemanfaatan Limbah Rumah Tangga menjadi Kompos - Suparjo; Kumala, Charisha Mahda; Adhi Danan, Yoga; Sri Sunarsih, Endang (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of this activity is to encourage increased household management skills in household waste processing in Kaliprau Village, Ulujami District, Pemalang Regency. The objectives are: 1) Increasing community/household knowledge about management, especially household/home waste processing; 2) Developing home business skills in household waste processing so that it grows into one of the drivers (centers) of family economic movement. The results of this activity: 1) Increasing knowledge, understanding and skills for household industry groups, especially in the utilization of household waste and making compost with household waste as raw materials; 2) Identified problems and potentials that can be developed to support the development of home businesses through entrepreneurship groups; 3) Identified plans (strategies) for increasing the capacity of entrepreneurship groups that will help develop, plan and utilize local potential management.